Exclusive breastfeeding for the first six months of life and its associated factors among children age 6-24 months in Burao district, Somaliland - Abdiasis Jama; Hailay Gebreyesus; Tewolde Wubayehu; Tsigehana Gebregyorgis; Mebrahtu Teweldemedhin; Tesfay Berhe; Negasi Berhe (BMC, 2020)
Abstract Background Adequate nutrition during early childhood ensures growth and development of children and breast milk is better than any other products given to a child. However, studies on exclusive breastfeeding practice are limited in Somaliland. Therefore, this study was aimed to assess exclusive breastfeeding for the first 6 months of life and its associated factors among children 6-24 months of age in Burao district, Somaliland. Methods A community-based cross-sectional study was conducted from 26 August to 10 October 2018, in Burao district among randomly, selected 464 mothers with children 6-24 months of age. Data were collected through face-to-face interview using pretested structured questionnaire. Results The prevalence of exclusive breastfeeding was 20.47% (95% CI 18.84, 23.63%). Exclusive breastfeeding practice was associated with: having female child (AOR 0.48; 95% CI 0.29, 0.80)), lack of formal education (AOR 0.32; 95% CI 0.19, 0.53), household monthly income 100$-200$ (AOR 0.35;95% CI 0.18, 0.68), lack of husband's support (AOR 0.32; 95% CI 0.19, 0.53), and mothers who were not counselled on breastfeeding during antenatal care (AOR = 0.33; 95% CI 0.16, 0.66). Conclusions Exclusive breastfeeding practice was very low as compared to recommendations of infant and young child practice (IYCF) which recommends children to exclusively breastfeed for the first 6 months of life. Exclusive breastfeeding practice was associated with a mother's lack of formal education, monthly income less than 100$, being a female child, lack of advice on exclusive breastfeeding during antenatal care and lack of husband support. The promotion of education for women, husband's engagement, encouraging antenatal care follow-up and counseling of exclusive breastfeeding during antenatal care was recommended to improve exclusive breastfeeding practice.